DESIGN AND DEVELOPMENT OF AN ANDROID-BASED FERTILIZER ORDERING APPLICATION IN THE BANGKALA REGION - Lutvi, Lutvi Karimah; Fathahillah, Fathahillah; Sidik Sidin, Udin (Fakultas Teknik Universitas Negeri Makassar, 2024)
In the Bangkala Region of Jeneponto Regency, farmers continue to depend on the conventional system for the fertilizer ordering process. This system results in inefficiencies and consumes the time of both sellers and buyers. We require an Android-based fertilizer ordering system that integrates directly with the server. The objective of this study is to develop an Android-based application for ordering fertilizer in the Bangkala region. This application was developed using the Research and Development (R&D) methodology and the waterfall development model. The results of this research have yielded a product in the form of an Android-based fertilizer ordering application, which will be utilized by farmers in the Bangkala Region, Jeneponto Regency. The system was tested using the ISO 25010 standard across four aspects: functional suitability, portability, usability, and performance efficiency. Functional suitability testing indicates that this application is